Nonvolatile resistive switching in Pt/LaAlO3/SrTiO3 heterostructures - Wu, Shuxiang (2014)
Resistive switching heterojunctions, which are promising for nonvolatile memory applications, usually share a capacitorlike metal-oxide-metal configuration. Here, we report on the nonvolatile resistive switching in Pt/LaAlO3/SrTiO3 heterostructures, where the conducting layer near the LaAlO3/SrTiO3 interface serves as the “unconventional” bottom electrode although both oxides are band insulators. Interestingly, the switching between low-resistance and high-resistance states is accompanied by reversible transitions between tunneling and Ohmic characteristics in the current transport perpendicular to the planes of the heterojunctions. We propose that the observed resistive switching is likely caused by the electric-field-induced drift of charged oxygen vacancies across the LaAlO3/SrTiO3 interface and the creation of defect-induced gap states within the ultrathin LaAlO3 layer. These metal-oxide-oxide heterojunctions with atomically smooth interfaces and defect-controlled transport provide a platform for the development of nonvolatile oxide nanoelectronics that integrate logic and memory devices.